A brief review of bio-inspired surface technology and application toward underwater drag reduction. (1st March 2020) - Liu, Guijie; Yuan, Zichao; Qiu, Zhaozun; Feng, Shuwen; Xie, Yingchun; Leng, Dingxin; Tian, Xiaojie
Abstract: Characteristics of creatures that have been evolved over long time in nature provide numerous inspirations to mankind for solving engineering problems. Inspired by biological principles, the development of bio-inspired surfaces for reducing the frictional resistance in fluid, such as the micro-groove surface of shark skin, the self-cleaning and antifouling surface of lotus leaf has attracted even more attention over the last couple of years. Based on the development of biomimetic drag reduction technology in recent decades, the present paper explains the morphology in brief and reviews the development of mainly three types of biomimetic surfaces, including non-smooth surface, superhydrophobic surface and water jet surface. The drag reduction effect and mechanism are discussed as well to understand the biomimetic drag reduction technology comprehensively. Moreover, the manufacturing methods are briefly summarized. In the end, the existing issues and future research priorities are proposed. This paper may provide a better comprehension of the current research status of bio-inspired drag reduction techniques. Highlights: Biomimetics is taken as the main line and the development of mainly three types of bio-inspired drag reduction surface is reviewed. The bottleneck of the current research is proposed by combing the main research results and the future research directions are pointed out. The research status and the future solutions of bio-inspired surface application toward underwater drag reduction are clearly reviewed.